Edukasi Kesehatan Reproduksi Dalam Format Digital: Gaya Komunikasi @dokteramiraobgyn di Platform TikTok - Nur Fadia Rusly; Farida Nurul Rahmawati (PT. ALHAFI BERKAH INDONESIA, 2025)
This study aims to analyze Doctor Amira's communication style in delivering reproductive health education through the TikTok platform. Amid the development of social media as the main means of disseminating health information, message delivery strategies are a key factor in building audience understanding and engagement. This study uses a descriptive qualitative approach with a content analysis method on several TikTok video contents owned by @dokter.amira that discuss topics of adolescent reproductive health. The results of the study indicate that Doctor Amira's communicative, emotional, and educational communication style not only increases digital engagement but also influences changes in the behavior of adolescent audiences. These findings contribute to the development of an effective social media-based health communication model that is relevant to the characteristics of the younger generation.